لترقية لدي الطلبة في المهارة الكلام ( Jigsaw ) طريقة تعليم جغسو - Banta Ali ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2017)
Jigsaw Comparative learning method is one of the special methods in the concentration of various knowledge disciplines of today. The process of learning and teaching requires adjustment in applying various methods to achieve maximum educational goals. The purpose of education will never be achieved unless by applying the correct and effective method. Therefore, "jigsaw" comparative learning methode aims to improve the ability of speaking (cooperative learning) ( ÙŠÙ†ÙˆØ§Ø¹ØªÙ„Ø§ Ù…Ù„Ø¹ØªÙ„Ø§) which includes influential factors in the internal and external classification of the subject of learning to improve student skills. Through the method of "cooperative learning" can affect students in learning language proficiency in groups. The improvement of students' speaking ability seemed very encouraging after applying this method when a lecturer gave them the task of memorizing vocabulary and understanding the content of a particular text. Comparative learning of this "jigsaw" model really gives maximum influence to students in communicating with Arabic.